Feed Enriched With Marigold Flower Meal to the Intensity of the Color of Guppies (Poecilia Reticulata) - *Harun Harun; Azwar Thaib; Nurhayati Nurhayati; Muhammad Haiqal; Suprihadi Suprihadi (Universitas Syiah Kuala, 2022)
Guppy fish (Poecillia reticulata) is a type of freshwater ornamental fish that is widely known and is an export commodity. The advantages of guppy fish include having interesting color variations and various fin patterns, easy to maintain and easy to breed. Male guppies have a higher economic value than female guppies. Because male fish have a more attractive shape and color than female fish. In order to increase the economic value of guppy fish, it is necessary to make efforts to increase the color intensity of guppy fish. This study aims to determine the color intensity of guppy fish (Poecilia reticulata) enriched with marigold flower flour. The experimental design used in the study was 2 treatments and 2 replications. Treatment A = Without marigold flower flour and Treatment B = Using marigold flower flour. Parameters observed were fish color measurement, weight growth, survival. The results showed that the addition of marigold flour had a significant effect on color intensity (p 0.05).